Buddhism and Thai Culture in the Northeastern Region of Thailand - Siriyan, Supachok (BUDDHO, 2025)
This study to examine the society, culture, and the role of Buddhism in shaping the way of life of communities in Lower Isan, comprising the Suay, Khmer, Lao, and Yer ethnic groups residing in Surin, Buriram, and Sisaket provinces. Within the context of globalization, these groups have adapted by reviving and preserving their cultural identities to support tourism and enhance local economic development. The findings reveal that the culture of Lower Isan is diverse in language, beliefs, customs, and rituals, with Buddhism serving as a central element that harmonizes traditional animistic beliefs and Brahmanism into a unique cultural identity. Community life is structured around the “Heet Sip Song – Khong Sip Si” system, a set of customs linking traditional festivals to agriculture, family relations, and communal living. However, the presentation of cultural identity in tourism remains limited in terms of distinctiveness and innovation, suggesting the need for creative development to enhance its value and appeal. Preserving and adapting cultural heritage based on local wisdom not only improves quality of life but also sustains ethnic identity and social cohesion in Lower Isan communities.